Temporal variation of vegetation at two operating landfills and its implications for landfill phytoremediation. Issue 5 (23rd February 2020) - Tao, Zhengkai; Shi, Wei; Liu, Yang; Chai, Xiaoli
ABSTRACT: Landfilling is a popular method to dispose of solid waste around the world, but this practice is associated with inevitable negative consequences such as air and water pollution and potential health hazards. Phytoremediation is an economical and promising technology to address these problems. To select suitable species for restoring landfills in China, the vegetation characteristics and their physiological activities were investigated in two different landfills. The results showed that the vegetation coverage of the two landfills both increased with the closure time. The species diversity decreased with the closure time in the Chongming landfill, whereas it showed the opposite trend in the Jiangcungou landfill. Five dominant species ( Conyza canadensis, Setaria viridis, Sesbania cannabina, Suaeda glauca, and Phragmites australis ) and four dominant species ( Festuca elata Keng, Amaranthus retroflexus, Lolium multiflorum, and Kochia scoparia ) were identified in the Chongming landfill and Jiangcungou landfill, respectively, and these dominant species were mainly annual plants. In addition, the net photosynthetic rate of P. australis and K. scoparia was the highest in the Chongming landfill and Jiangcungou landfill, respectively. Their photosynthetic rates were influenced significantly by stomatal conductance. Based on the overall results, among the dominant species identified, P. australis and K. scoparia represent potentially well suited plants to use in the remediation of landfills in China, because of their strong adaptability to landfill environments and natural occurrence in landfills. GRAPHICAL ABSTRACT: